ANALISA NILAI KETANGGUHAN HASIL PENGELASAN PADA SAMBUNGAN PIPA DENGAN PREHEAT DAN TANPA PREHEAT - Magga, Ramang (MEKTEK, 2008)
This paper aim to analyze the effect of preheat in welding process of pipe joints on weld strength value .speciment which tested in strength and micro structures show that the process with out preheat before welding have bigger strength than process with preheat ,particularly seen HAZ area